EXERCISE TESTS IN CARDIOLOGY: PAST, PRESENT AND FUTURE. PART II - V. P. Voronina; N. V. Kiseleva; S. Yu. Martsevich (Кардиоваскулярная терапия и профилактика, 2015)
The second part of the review focuses on the main principles of exercise tests, protocols of exercise tests, prognostic significance of the values obtained in ischemic heart disease. The problems are accounted on how to use the results of exercise tests for pretest probability of ischemic heart disease, to stratify the risk of cardiovascular complications, to evaluate the efficacy and prognosis.